Meningkatkan Hasil Belajar Fisika Melalui Model Pembelajaran Kontekstual Tipe Problem Based Learning Materi Arus Listrik Searah - Saepullah (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
Based on learning outcomes data for class XII IPA 1 SMA Negeri 15 Pandeglang withdirect current electricity material (data for the 2021/2022 school year), students' physics learningoutcomes cannot be said to be good because as many as 100% of students are below the MinimumCompletion Criteria or KKM score. The average value is only at number 51 with the smallestvalue is 20 and the largest value is 77. The purpose of this study is: to determine whether the useof contextual learning model type problem -based learning can improve physics learningoutcomes. The method of Classroom Action Research (CAR) or commonly referred to as(classroom action research), the contextual learning approach is a contextual learning model typeproblem-based learning direct current electricity material in class XII IPA 1 SMA Negeri 15Pandeglang the research results state that by using the model contextual learning of the type ofproblem-based learning can improve student learning outcomes in physics learning on directcurrent electricity. The success rate of students increases every cycle. In the first cycle of 57%, inthe second cycle there was an increase of 77.14%, while in the third cycle there was an increaseof 100%.